The Effectiveness Of People's Business Credit (KUR) In Sugarcane Farming In West Java Province - Dina Dwirayani; Nunung Nuryartono; Dwi Rachmina; Amzul Rifin (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
People's Business Credit (KUR) is a credit scheme intended for farmers since 2000. The availability of credit for business actors is used to increase capital. However, not all credit obtained can be categorized as effective. Credit is effective if farmers can receive benefits from the disbursement and use of credit to meet farming activities, and one of which is increasing productivity.. This study aims to analyze the effectiveness of KUR for sugarcane farmers in West Java Province. This research uses a quantitative descriptive analysis method using scoring. The results showed that the average score of timely credit effectiveness was 103%.. The timeliness score is greater than 100%, meaning that the average credit is on time. Credit is already available before farmers start farming, so that on average, all farming activities can be carried out on time, except for the procurement of fertilizer and cultivation costs. The average accuracy of the amount of credit with the realization of expenditure is 85%, below 100%. This means that credit for the procurement of inputs and farming activities is still not effective, especially for the amount of fertilizer and herbicides. The level of effectiveness of sugarcane farmer credit is at a score of 87.3% to 106.1%, with an average farmer credit effectiveness rate of 94%.  This means that, on average, farmers have credit that is ineffective. Most farmers are late in receiving credit disbursements, and the amount of credit received is less than their farming needs.